FORMULASI KRIM ANTIOKSIDAN EKSTRAK ETANOL BAWANG HUTAN (ELEUTHERINE PALMIFOLIA L. MERR) - Sharon, Nela; Anam, Syariful; Yuliet, Yuliet (Natural Science: Journal of Science and Technology, 2013)
Eleutherine palmifolia L. Merr having antioxidant activity, its because of contain flavonoid, fenolat and tanin. These compounds have effect in  preventing of free radical which cause premature aging. Research on ethanol extract of E. palmifolia L. Merr which formulated into antioxidant cream have been done by applying variation of TEA emulgator and stearic acid. That variation  were F1 (2% : 6%), F2 (3% : 12%) and F3 (4% : 18%). Determination of antioxidant activity  was done based on DPPH methode, and the Value is 98,210%. Furthermore, evaluation on  physical characteristics was done based on organoleptic test, homogenity, pH, viscosity and stability of cream preparation. Observation was done during 21 days. Obtained data were then analyze by student-t test in comparing of the value between fresh and 21 days after storage. the pH of cream F1, F2 and F3 were not showed significant decrease, while DPPH reduce percent of F1, F2 and F3 were showed significant decrease.  In contrast, viscosity of cream F3 was significant decrease. Antioxydant activity extract based on DPPH reduce percent value of F1, F2, F3 at the first day were 96,822%, 97,123% and 96,896%, respectively. Whereas that value  at 21nd days after storage  were 89,036%, 89,726% and 90,564%, respectively.  Our result showed that E. palmifolia L. Merr ethanol extract  can be formulated as a cream preparations. F2 physical properties was  fullfill standart quality, which it was used TEA emulgator and stearic acid proportion of 3% : 12%.